Pengembangan Model Pembelajaran Sepakbola dengan Permainan â€œBalangkaâ€ (Department of Physical Education, Sport, Health and Recreation, 2015)
This research aims to determine the results of learning model development through the game of football balangka for eighth-grade students of SMP Negeri 1 Semarang in learning Physical education and HealthThe method of this research is to development refers to developing the model. (research-based development) by Brog and Gall that has been modified. The data was collected by a questionnaire derived from, expert evaluation, the observation sheet student movement, a small test group (12 students), and range tests (30 students). Research data, expert evaluation data that experts physical education 80% (it means good), learning experts 89.33% (it means excellent), observational data motion test students' small group 92.67% (it means excellent), observational data field test student movement, 96.67% (it means very good), a small group of test result data from the student questionnaire obtained a percentage of 86.67% (excellent), the data from the field test results of the student questionnaire obtained a percentage 84.89% (it means excellent). Based on the results in above, the concluded is balangka game development learning model is compatible to applied for both eighth-grade students of SMP Negeri 1 Semarang